Boundary layer flow and heat transfer over a permeable shrinking cylinder with surface mass transfer - Bhattacharyya, K.; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, the axisymmetric boundary layer flow and heat transfer past a permeable shrinking cylinder subject to surface mass transfer is studied. The similarity transformations are adopted to convert the governing partial differential equations for the flow and heat transfer into the nonlinear self-similar ordinary differential equations and then solved by a finite difference method using the quasilinearization technique. From the current investigation, it is found that the velocity in the boundary layer region decreases with the curvature parameter and increases with suction mass transfer. Moreover, with the increase of the curvature parameter, the suction parameter and Prandtl number, the heat transfer is enhanced
Keywords: boundary layer; heat transfer; shrinking cylinder; mass suction